RESPONSIVITAS PELAYANAN PUBLIK TERHADAP PASIEN BPJS DI PUSKESMAS GANTIWARNO KABUPATEN KLATEN - Prasetyo, Firlo Erwin Yudi; Yunanto, Mohammad Kus (PARADIGMA: Jurnal Ilmu Administrasi, 2024)
The responsiveness of public services is a key indicator of quality in healthcare, particularly for patients using BPJS, Indonesia's national health insurance program. This study examines the responsiveness of public services provided to BPJS patients at the Gantiwarno Community Health Center in Klaten Regency. Through a qualitative approach, data were collected from both BPJS patients and healthcare providers to understand service satisfaction levels, response times, and challenges faced. Findings indicate varying levels of responsiveness, influenced by factors such as staff workload, resource availability, and administrative processes. The study concludes with recommendations for improving responsiveness and enhancing service quality for BPJS patients, which may lead to better healthcare outcomes and increased patient satisfaction. These insights provide valuable guidance for policymakers and healthcare providers in optimizing public health services in community health centers.Keyword: Responsiveness; Public Services; Healthcare; BPJS Patients.